Pneumonia in Nigeria: The way forward. Issue 1 (12th May 2020) - Wonodi, Chizoba; Obi‐Jeff, Chisom; Falade, Adegoke; Watkins, Kevin; Omokore, Oluseyi A.
Abstract: Pneumonia is the leading cause of child deaths in Nigeria. Interventions to combat pneumonia are known and globally available, but not yet deployed effectively in Nigeria. While the under‐five pneumonia deaths dropped globally by 51% during the Millennium Development Goals (MDG) years (2000 to 2015), the rate declined by a mere 8% in Nigeria. In this commentary, we focus on three factors that may have stalled Nigeria's progress on pneumonia control. First, a chronically weak health system failed to deliver the needed services at scale. Second, strong coordination of a multipronged and well‐funded push against pneumonia was absent. Third, sound and timely data on pneumonia intervention coverage were lacking, thus blunting the accountability mechanisms that could have driven quick, targeted action. In response, the Federal Ministry of Health recently developed a National Pneumonia Control Strategy with the support of the "Every Breath Counts Coalition" (EBCC). This strategy, a first of its kind, articulates a common vision for reducing pneumonia‐led morbidity and mortality and provides a unified approach to respond comprehensively to pneumonia within and outside the health sector. Strong political will and sustainable financing are now needed to effectively implement this strategy and accelerate progress on pneumonia control. This will contribute hugely to achieving the government's health goals, the Sustainable Development Goal (SDG) 3.2 and the Global Action Plan on Pneumonia and Diarrhoea (GAPPD) targets.